Efektivitas Air Rebusan Seledri (Apium graveolens) sebagai Terapi Komplementer dalam Menurunkan Tekanan Darah pada Pasien Hipertensi - Arun Aruna; Nur Wahyuni Munir; Safruddin; Rahmat Hidayat (Pusat Kajian dan Pengelola Jurnal FKM UMI, 2026)
Hypertension is a condition where systolic blood pressure is ≥ 140 mmHg and diastolic blood pressure is ≥ 90 mmHg. This study aims to determine the effect of boiled celery water on reducing blood pressure in hypertension sufferers in Waipare a Maumere, East Nusa Tenggara. This type of research uses an experimental research design using a research design, namely a non-equivalent control group design This study used an intervention group and a control group. The sample in this study was 46 people and was divided into two groups, namely the intervention group 23 people and the control group 23 people. The intervention group will be given therapy to drink 40 grams of boiled celery water with 150 cc each in the morning and evening for 1 week. Data analysis used paired t-test and independent t-test. The results of the paired t-test statistical test for the celery boiled water intervention group were effective in reducing blood pressure with a p value <0.05 with a decrease in systolic 36.8 mmHg and diastolic 12.0 mmHg, meaning that giving boiled celery water had an effect on reducing blood pressure in hypertension sufferers. Meanwhile, the results of the independent t-test showed that the p value for the intervention group was p= 0.001 with a decrease in systolic of 36.8 mmHg and diastolic of 12.0 mmHg, whereas for the control group the decrease in systolic was 0.21 mmHg and diastolic was 1.04 mmHg, meaning water treatment Celery decoction is more effective in reducing blood pressure in hypertension patients. The conclusion is that giving boiled celery water has been proven to have an effect on reducing blood pressure in hypertension sufferers.